2002
DOI: 10.1128/iai.70.6.2780-2786.2002
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Differentiation in Localized Juvenile Periodontitis Is Skewed toward the Dendritic Cell Phenotype

Abstract: Several lines of evidence indicate that the monocytes of subjects with localized juvenile periodontitis (LJP) are functionally distinct from cells of age-and race-matched nonperiodontitis (NP) subjects. Among the abnormalities are the propensity to secrete large amounts of prostaglandin E 2 and the induction of immunoglobulin G2 (IgG2) antibodies. The experiments described here were performed to further characterize the LJP monocytes and to determine if these cells mature differently than NP monocytes. When ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
(46 reference statements)
3
34
0
Order By: Relevance
“…Most notably, the monocyte-derived lipid mediators, PAF and PGE 2 , were shown to induce IgG2 production, but had no effect on the production of IgG1 in a pokeweed mitogen-driven in vitro culture system. Furthermore, highly enriched MDDC cultures were shown to have a similar selective effect on IgG2 production (9). Together, these studies suggest that the outgrowth of MDDC in cultures of LJP monocytes may have important implications for the regulation of Ig subclass responses and that this regulation may be mediated through the levels of lipid mediators in the cultures.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Most notably, the monocyte-derived lipid mediators, PAF and PGE 2 , were shown to induce IgG2 production, but had no effect on the production of IgG1 in a pokeweed mitogen-driven in vitro culture system. Furthermore, highly enriched MDDC cultures were shown to have a similar selective effect on IgG2 production (9). Together, these studies suggest that the outgrowth of MDDC in cultures of LJP monocytes may have important implications for the regulation of Ig subclass responses and that this regulation may be mediated through the levels of lipid mediators in the cultures.…”
mentioning
confidence: 72%
“…Our interest in PAF metabolism in MDDC comes from studies of the immune response in localized juvenile periodontitis (LJP), a periodontal disease characterized by its circumpubertal onset and characteristic localized loss of supporting tissues around first molars and incisors (8). In a previous study we demonstrated that monocytes from LJP subjects have an increased propensity to differentiate into MDDC, while monocytes from healthy non-periodontitis (NP) subjects primarily differentiate into M (9). Moreover, LJP subjects have elevated levels of IgG2 Ab in their sera, and LJP monocytes secrete cytokines that selectively promote the production of this subclass of Ab (10,11).…”
mentioning
confidence: 99%
“…IgG2 levels in supernatant fluids were determined by a sandwich ELISA as described previously (4). Briefly, Fc-specific goat anti-mouse antibody (10 l/ml) (ICN, Aurora, Ohio) in pH 9.6 carbonate buffer was used to coat the microtiter plates (Dynex, Chantilly, Va.).…”
Section: Methodsmentioning
confidence: 99%
“…2A and B). These observations are of particular interest because monocyte differentiation appears to be skewed to the DC phenotype in LAgP subjects (4). Indeed, PAFAH levels are lower in the adherent monocytes of LAgP subjects than in monocytes from race-matched NP controls (1).…”
mentioning
confidence: 98%
“…In blood, or in sites infiltrated with blood, NK cells are the source of this rapid IFN-γ (24-hour) that promotes DC-IL-12. NK cells need IL-12 for Barbour et al (2002) optimal IFN-γ, and it appears that P. gingivalis-DC-NK interactions result in reciprocal activation and increased DC-IL-12 and NK cell-IFN-γ (Kikuchi et al, 2004(Kikuchi et al, , 2005(Kikuchi et al, , 2010. Both DCs and NK cells are necessary to get the rapid 24-hour IFN-γ needed to induce the P. gingivalis-specific IgG2 in recall responses in PBL cultures (Kikuchi et al, 2005).…”
Section: Pro-inflammatory Cytokines and Igg2 Responsesmentioning
confidence: 99%